INFECTION AFTER ARTHROSCOPIC ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION: DIAGNOSIS AND TREATMENT OUTCOMES. (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluation of Treatment Outcomes for Infections Following Arthroscopic Anterior Cruciate Ligament Reconstruction at Hanoi Medical University Hospital.Subjects and Methods: A retrospective descriptive study was conducted on 18 patients diagnosed with infection after arthroscopic anterior cruciate ligament reconstruction at Hanoi Medical University Hospital from March 2021 to March 2025.Results: The study included 18 patients with a mean age of 29.83 ± 9.79 years (range 16–44), with a male-to-female ratio of 5:1. The mean time to symptom onset was 19.41 ± 23 days. Clinically, 100% of patients presented with swelling, warmth, pain, and restricted range of motion. Regarding laboratory findings, both blood tests and synovial fluid analysis demonstrated markedly elevated leukocyte counts exceeding diagnostic thresholds. CRP and ESR levels were also significantly elevated. Medical treatment followed IDSA (2013) and AAOS (2020) recommendations for postoperative septic arthritis, using a combination of Vancomycin with either a third-generation cephalosporin or Clindamycin. The mean duration of antibiotic therapy was 32.94 ± 19.07 days. For surgical management, the graft removal group demonstrated better infection control compared with those treated with arthroscopic debridement alone. Successful graft retention yielded the most favorable functional outcomes (Lysholm 88.5 ± 3.74) and avoided reoperation. Although graft removal effectively controlled infection, 100% of these patients required subsequent reconstructive surgery, particularly in younger and more active individuals. At final follow-up, 100% of patients achieved complete infection resolution after prolonged antibiotic therapy, consistent with IDSA (2013) guidelines.Conclusion: Postoperative infection following arthroscopic ACL reconstruction is uncommon but can lead to serious impairment of knee function. Early diagnosis and aggressive management facilitate graft preservation and favorable recovery.
Keywords: Anterior cruciate ligament; Knee arthroscopy; Knee joint infection; Sports injuries.